What Do P-Wave Velocities Tell Us About the Critical Zone? - Flinchum, Brady A.; Holbrook, W. Steven; Carr, Bradley J. (Frontiers in Water, 2022)
Fractures in Earth’s critical zone influence groundwater flow and storage and promote chemical weathering. Fractured materials are difficult to characterize on large spatial scales because they contain fractures that span a range of sizes, have complex spatial distributions, and are often inaccessible. Therefore, what we 'see' in the critical zone depends on the scale of our tool, and the response of the medium to impulses at that scale. Using P-wave velocities collected at two scales, we show that seismic velocities in the fractured bedrock layer of the critical zone are scale-dependent. The smaller-scale velocities, derived from sonic logs with a dominant wavelength of ~0.3 m, show substantial vertical and lateral heterogeneity in the fractured rock, with sonic velocities varying by 2000 m/s over short lateral distances (~0.7 m), indicating strong spatial variations in porosity or fracture density. In contrast, the larger-scale velocities, derived from seismic refraction surveys with a dominant wavelength of ~50 m, are notably slower than the sonic velocities (a difference of ~3000 m/s) and lack lateral heterogeneity. We show that this discrepancy is a consequence of contrasting measurement scales between the two methods; in other words, the contrast is not an artifact but rather information -- the signature of a fractured medium (weathered/fractured bedrock) when probed at vastly different scales. We explore the sample volumes of each measurement and show that surface refraction velocities provide reliable estimates of critical zone thickness but are relatively insensitive to lateral changes in fracture density at scales of a few 10’s of meters. At depth, converging refraction and sonic velocities likely indicate the top of unweathered bedrock, indicative of material with similar fracture density across scales.